2014
DOI: 10.1111/ijcp.12466
|View full text |Cite
|
Sign up to set email alerts
|

Development of SLE among “potential SLE” patients seen in consultation: long-term follow-up

Abstract: Objective To identify factors associated with development of systemic lupus erythematosus (SLE) among patients evaluated at a tertiary care Lupus Center for potential SLE Methods We identified patients first seen at the Brigham and Women's Hospital Lupus Center between January 1, 1992 and December 31, 2012 and thought to have potential SLE by a board certified rheumatologist. All had 1-3 SLE ACR criteria at initial visit and >2 follow-up visits ≥ 3 months apart. We reviewed medical records through May 15, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 12 publications
0
43
1
4
Order By: Relevance
“…One change in the 2012 criteria is the loss of photosensitivity as a separately scored point. Photosensitivity is a frequent feature of patients with unclassifiable lupus-like syndromes, present in more than 20% of these patients [17], but the loss of this as a separate criterion did not appear to have a great impact on the ILE scores in the present study. Another change in the 2012 criteria is the addition of low complement as scored item.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…One change in the 2012 criteria is the loss of photosensitivity as a separately scored point. Photosensitivity is a frequent feature of patients with unclassifiable lupus-like syndromes, present in more than 20% of these patients [17], but the loss of this as a separate criterion did not appear to have a great impact on the ILE scores in the present study. Another change in the 2012 criteria is the addition of low complement as scored item.…”
Section: Discussioncontrasting
confidence: 58%
“…In clinical care, repeated and inconclusive evaluations may go on for many years. In one cohort, 56% of patients identified as “potential” SLE remained in that category after a mean of 6.3 years of followup [17]. This long period of diagnostic uncertainty may explain the somewhat surprising finding of the self-assessment responses in the ILE group reported here, showing that these patients thought that they were actually worse than they had been a year previously, even though a diagnosis of a more serious illness, SLE, had not been made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "undifferentiated connective tissue disease" (UCTD) has been used to refer to individuals presenting with clinical symptoms suggestive of some autoimmune CTD (SLE, Sj€ ogren's syndrome, scleroderma, mixed CTD, or RA), but not clearly meeting ACR classification criteria for any of these diseases, a common clinical scenario. Followup studies of UCTD patients have revealed the rates of progressing to SLE are very similar to those in incomplete lupus cohorts, approximately 20% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Additionally, those patients who have a prolonged clinical onset of their SLE tend to have a mild disease course without severe organ involvement (10).…”
mentioning
confidence: 97%
“…In patients suspected of having SLE but not fulfilling ACR classification criteria, the presence of oral ulcers, renal disease (defined by as persistent proteinuria, cellular casts, or both), and anti-doublestranded DNA antibodies were predictors of evolution to definite SLE. 9 Although not everyone with a positive ANA requires evaluation by a rheumatologist, in cases of uncertainty, it may be helpful to refer patients to a rheumatologist for evaluation. Testing all patients with a positive ANA for thyroid-specific antibodies is unnecessary and should be at the discretion of the evaluating physician.…”
Section: Application Of Test Results To This Patientmentioning
confidence: 99%